2015
DOI: 10.1007/s10884-015-9438-x
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical System Associated with the Fixed Points Set of a Nonexpansive Operator

Abstract: We study the existence and uniqueness of (locally) absolutely continuous trajectories of a dynamical system governed by a nonexpansive operator. The weak convergence of the orbits to a fixed point of the operator is investigated by relying on Lyapunov analysis. We show also an order of convergence of o 1 √ t for the fixed point residual of the trajectory of the dynamical system. We apply the results to dynamical systems associated with the problem of finding the zeros of the sum of a maximally monotone operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…In particular, by combining (13) with (15), we deduce that lim t→+∞ z(t) − z 2 exists. Applying Opial's lemma [10,Lemma 4] then shows that z(t) converges weakly to a pointz ∈x+ λB(x) wherē x is a weak sequential cluster point of x(t). The definition of J λB then yieldsx = J λB (z), which implies that J λB (z) is the unique cluster point of x(t).…”
Section: From the Discrete To The Continuousmentioning
confidence: 99%
“…In particular, by combining (13) with (15), we deduce that lim t→+∞ z(t) − z 2 exists. Applying Opial's lemma [10,Lemma 4] then shows that z(t) converges weakly to a pointz ∈x+ λB(x) wherē x is a weak sequential cluster point of x(t). The definition of J λB then yieldsx = J λB (z), which implies that J λB (z) is the unique cluster point of x(t).…”
Section: From the Discrete To The Continuousmentioning
confidence: 99%
“…In [20], it was shown that many convex minimization and monotone inclusion problems reduce to the more general problem of finding a fixed point of compositions of averaged operators, which provided a unified analysis of various proximal splitting algorithms. Along these lines, several fixed point methods based on various combinations of averaged operators have since been devised, see [1,2,5,9,11,13,14,17,18,24,25,38,46] for recent work. Motivated by deep neural network structures with thus far elusive asymptotic properties, we investigate in the present paper a novel averaged operator model involving a mix of nonlinear and linear operators.…”
Section: Introductionmentioning
confidence: 99%
“…Cocoercivity arises in various areas of optimization and nonlinear analysis (see, e.g., [1,6,7,12]). In particular, it plays an important role in the design of algorithms to solve structured monotone inclusions (which includes fixed points of non-expansive operators).…”
Section: Introductionmentioning
confidence: 99%
“…The previous result was extended by Boţ and Csetnek (see [7,Theorem 12]) to solve the monotone inclusion: find x ∈ H such that…”
Section: Introductionmentioning
confidence: 99%